Fitness Trends and Disparities Among School-Aged Children in Georgia, 2011-2014 - Bai, Yang (Public Health Rep, 2017)
OBJECTIVES: Although FitnessGram fitness data on aerobic capacity and body mass index (BMI) have been collected in public schools in Georgia since the 2011-2012 school year, the data have not been analyzed. The primary objective of our study was to use these data to assess changes in fitness among school-aged children in Georgia between 2011 and 2014. A secondary objective was to determine if student fitness differed by school size and socioeconomic characteristics. METHODS: FitnessGram classifies fitness into the Healthy Fitness Zone (HFZ) or not within the HFZ for aerobic capacity and BMI. We used data for 3 successive school years (ie, 2011-2012 to 2013-2014) obtained from FitnessGram testing of students in >1600 schools. We calculated the percentage of students who achieved the HFZ for aerobic capacity and BMI. We used growth curve models to estimate the annual changes in these proportions, and we determined the effect of school size and socioeconomic status on these changes. RESULTS: Both elementary school boys (β = 1.31%, standard error [SE] = 0.23%, P < .001) and girls (β = 1.53%, SE = 0.26%, P < .001) had significant annual increases in achievement of HFZ for aerobic capacity. Elementary school boys (β = 3.11%, SE = 0.32%, P < .001) and girls (β = 3.09%, SE = 0.32%, P < .001) also had significant increases in their BMI HFZ achievement proportions, although these increases occurred primarily between 2011-2012 and 2012-2013. Body mass index HFZ achievement proportions were mixed for middle school students, and we did not observe increases for high school students. Larger school size and higher school socioeconomic status were associated with better aerobic capacity and BMI fitness profiles. CONCLUSIONS: Surveillance results such as these may help inform the process of designing state and local school-based fitness promotion and public health programs and tracking the results of those programs.